Perfil adipogênico do tecido adiposo branco de camundongos submetidos a diferentes modalidades de treinamento - Gilio, Gustavo Renan (2016)
The white adipose tissue is a metabolic organ with wide plasticity. The adipocyte stores a great lipid volume of triglycerides being adipogenesis sensitive to external factors such as physical exercise. In addition, exercise modulation of adipogenesis is poorly understood when comes to influence of different exercise types. Therefore, the aim of this study was to determine the adipogenic profile of different white adipose tissue depots of mice submitted to different training modalities. The experimental protocol was conducted using 80 male swiss mice, 45 days old, grouped as follow: sedentary control (SED) (n=20), aerobic training treadmill (AER) (n=21), resistance training ladder (RES) (n=19) and combined training (COM aerobic and resistance) (n=20). Animals had free access to water and food. Physical training was realized 5x/week, throughout 8 weeks. After the end of experimental protocol, the animals body weight and naso-anal length (Lee s index) were determined, RET, MES, EPI, e ING were collected and weighed, the RET, EPI e ING fat pad were fixed in paraformaldehyde, embbed in paraffin, cut and stained in hematoxylin and eosin to measure adipocyte area. The RET e ING fat pad total RNA were extracted, amplified and quantified by real time PCR in order to determine PPARγ, C/EBPα, Pref1 e Perilipin mRNA expression. The data normalities were determined, ANOVA one-way test (Tukey post-hoc) and Kruskal Wallis (Dunns post-hoc) were used to calculate the different magnitude among the groups, adopting P<0,05. The results were provided as mean and mean standard error. Moreover, size effect by Cohen d was used, being values >0.8 or <-0.8 considered as great size effect . The results show that: the RES group was the only one who had lower body weight; AER, RES and COM lower weight in visceral fat pad and RES and COM lower weight on the ING fat pad, all of them compared to the SED group. There was no statistical difference for adipocytes area among the groups. However, the RES and groups showed large effect size (<-0.8) to the area of adipocytes compared to the SED group in RET, EPI and ING whilst the AER group only in EPI and ING fat pad (<-0.8). For gene expression (mRNA), There was no statistical difference in any mRNA for the AER group or to any group in the RET fat pad, but the RES group showed lower expression of PPARγ and COM group lower expression of C/EBPα and perilipin, both compared to the SED group to ING fat pad. At the effect size of gene expression, the RES and COM groups showed large effect size for C/EBPα (> 0.8) and the AER group for Pref1 mRNA (<-0.8). The RES and COM groups also had large effect size for the expression of PPARγ, C/EBPα and perilipin mRNA (<-0.8) in ING fat pad. From the results we can see the resistance and combined training stood out because they could reduce the weight of visceral and subcutaneous cushions. The combined training seems to be the best option to reduce adipogenic factors (from the smaller gene expression of C / EBPα and perilipin), as well as the isolation resistance training to lower expression of PPARγ, both in the inguinal fat pad (subcutaneous). Thus, we can conclude that the type of training and the fat pad seem to influence the patterns of analyzed adaptations. In summary, resistance and combined exercise training is a powerful stimulus for modulating adipogenesis in vivo.